Estrutura e função biológica da Sulfonamida Chalcona c28h19o3nbrscl - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Cristal is an interdisciplinary science capability, capable of contributing to different areas of science, through its ability to elucidate molecular structure, capable of understanding the relationship established between structuration and activity. As examples of large biomolecules in the technique, such as chalcones and their simple potentials and structures with biological synthesis, current works were described, among which environmental applications are possibilities. Through the structural structure of chalcones, through the characterization of x-ray differentiation, it is possible to know the structural aspects, interatomic distances and possible predictions of probable biological actions. Allied to crystallography, the Virtual Screening, applicable methodology for building models in silicon for the knowledge under such characteristics. In this work, the structural characteristics and theoretical predictions of an unprecedented structure of chalcone sulfonamide were presented. For measurements, methodologies such as crystallographic, HS surfaces, DFT analysis, pharmacophoric groups and molecular docking were used. The results demonstrate that the compound has kinetic stability for EGFR activity and analysis that has effective pharmacological characteristics for the potential as a suggestion of EGFR gene antagonist, making antineoplastic action. This result, which is a molecule, has a complementary treatment with the five most important EGFR antagonists, which are LYS745, ALA743, CYS797 and VAL726. Based on these theoretical predictions, the new theoretical chalcone described is an excellent candidate for future in vitro and in vivo tests for further production of a drug specific to this gene.
Structure and biological function of Sulfonamide Chalcone c28h19o3nbrscl
Keywords: Virtual Screening; Difração de Raios X; Estrutura-atividade; Chalconas; Ciências ambientais; Docking molecular; Virtual Screening; X-Ray Diffraction; Activity-structure; Chalcones; Environmental sciences; Docking molecular; CIENCIAS BIOLOGICAS::BIOFISICA